The Global Financial Crisis, Inflation Rate And Stock Market Returns In Kenya - Donald A. Otieno; Rose W. Ngugi; Nelson H. W. Wawire (European Scientific Journal, ESJ, 2017)
The moderating effect of events such as the 2008 Global Financial Crisis (GFC) on the relation between stock market returns and macroeconomic variables has attracted very little attention. This study investigates the extent to which the 2008 GFC moderated the relationship between inflation rate and stock market returns. The study uses month-onmonth inflation rate and year-on-year inflation rate from 1st January 1993 to 31st December 2015 and divides the sample data into pre-crisis period (from 1st January 1993 to 31st December 2007); crisis period (from 1st January 2008 to 30th June 2009); and post-crisis period (from 1st July 2009 to 31st December 2015). It uses a product-term regression model instead of the most widely applied additive regression model. Results indicate that a unit increase in the both measures of inflation rate had significant depressing effects on stock market returns after the crisis compared to before the crisis. Likewise, the results reveal that average stock market returns were significantly higher after the crisis compared to before the crisis at low rather than medium or high values of the two measures of inflation rate. These results suggest that the Kenyan stock market is highly sensitive to variations in inflation rate, especially as it emerges from a financial or political turmoil. This study is empirically innovative in the sense that it is the first to examine the moderating effect of the 2008 GFC on the relation between inflation rate and stock market returns in Kenya using a product-term model.